ASESMEN, PERKUATAN DAN PERBAIKAN BANGUNAN NON-ENGINEERED PERUMAHAN MEKAR MELATI KELURAHAN LUBUK MINTURUN KOTA PADANG PASCAGEMPA 2009 - Rafki I Imani; Sofia Anita; Sonya Ostha Laurency; Fakhru Rozi (Construction and Material Journal, 2020)
The West Sumatra Earthquake on September 30, 2009, which also hit Padang City, caused most of the buildings to be severely and slightly damaged. This paper discusses the types of damage, repairs and reinforcement of residential houses in Mekar Melati Housing, Lubuk Minturun Sub-District, Padang City, West Sumatra. Data were collected using direct survey and assessment on both houses that have been severely damaged or slightly damaged. After the 2009 earthquake, the residential houses in the Mekar Melati housing complex in Lubuk Minturun, generally suffered severe damage and slight damage. The reason is that the building there is included in the category of very simple houses. Building materials used without slof, let alone walls that only use hollowbrick material, of which if the material is not plastered it will become brittle, resulting in the building easily collapsing. Keywords: Damage, Earthquake, Residential Houses, Repairs and Reinforcement.